KEADILAN BERKONTRAK DALAM REFORMULASI HUKUM INFORMED CONSENT BERBASIS KEADILAN SOSIAL - Aryoko Abdurrachman; Isharyanto; I Gusti Ayu Ketut Rachmi Handayani Handayani (Program Pascasarjana Fakultas Hukum Universitas Sebelas Maret Surakarta, 2018)
AbstractThis paper discusses necessary contracted justice on informed consent reformulation based on social justice in physician and patient relationships. The necessary begins from the absence of justice for physician and patient in the actualization of Informed Consent. Relevant legislation is not based on justice. This paper is a presciptive legal research with approach of law and conceptual approach. The technique of collecting legal materials in this paper is literature study. The technique of analysis of legal materials used is the method of deduction. This paper concludes a review of Law No. 29 of 2004 on Medical Practice to accommodate the contracted justice in Informed Consent based on social justice. This paper recommended Article 2 of the a quo law the formula is changed to be